2019
DOI: 10.1103/physrevaccelbeams.22.103101
|View full text |Cite
|
Sign up to set email alerts
|

Vertical electropolishing for 1.3 GHz single- and nine-cell superconducting niobium cavities: A parametric optimization and rf performance

Abstract: Electropolishing (EP) is a standard process for the treatment of the interior surface of niobium (Nb) superconducting radio-frequency (SRF) cavities used in particle accelerators. We previously conducted a study on vertical electropolishing (VEP), in which the cavity was set vertically during EP of a 1.3 GHz Nb single-cell cavity. In that study, we showed that the major cause of asymmetric removal in VEP is the accumulation of hydrogen gas bubbles, generated during the EP process, on the upper half cell of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Consequently, the average I-V curve in EP might reach a plateau at a lower voltage than that required for the equator surface. An EP study conducted on a 9-cell cavity demonstrated notable differences between the average I-V curve and measurements obtained solely from isolated coupons located at the equator, as described in my paper [2].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Consequently, the average I-V curve in EP might reach a plateau at a lower voltage than that required for the equator surface. An EP study conducted on a 9-cell cavity demonstrated notable differences between the average I-V curve and measurements obtained solely from isolated coupons located at the equator, as described in my paper [2].…”
Section: Discussionmentioning
confidence: 69%
“…Electropolishing (EP) is a widely utilized technique for treating metal surfaces. It is commonly employed to process niobium made superconducting radiofrequency (SRF) cavities [1][2][3], which are key components in particle accelerators. These cavities are operated at high frequencies, typically ranging from several hundred megahertz to a few gigahertz, in order to accelerate charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Standard mechanical polishing can provide very smooth surfaces but a damaged layer (about 100 µm on Nb) is still present at the surface. Buffered chemical polishing (BCP) and electropolishing (EP) are conventional methods used to remove the damaged layer and prepare cavities [9,10]. BCP is composed of acids such as HNO 3 , H 3 PO 4 , and HF at a typical 1:2:1 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The cavity could be used for parameter optimization in conjunction with RF tests of actual cavities with the corresponding geometry, to help provide an understanding of how the parameters are affecting the local microstructure and connect that to the overall RF performance. Sample-host cavities have been used in the past to study other SRF processing techniques (Cooper and Cooley 2013, Lee et al 2017, Chouhan et al 2019 From a materials science perspective, the Nb 3 Sn vapor diffusion process is not well understood. There are a number of empirical observations that have been made in the past that have led to the coating procedures currently used.…”
Section: Introductionmentioning
confidence: 99%